ARTcode: Preserve Art and Code in Any Image - Yang, Zhe; Bao, Yuting; Luo, Chuhao; Zhao, Xinya; Zhu, Siyu; Peng, Chunyi; Liu, Yunxin; Wang, Xinbing (The 2016 ACM International Joint Conference on Pervasive and Ubiquitous Computing (UbiComp 2016), 2016)
The ubiquitous QR codes and some similar barcodes are becoming a convenient and popular approach to impromptu communication between mobile devices and their surrounding cyber-physical world. However, such codes suffer from two common drawbacks: poor viewing experience and inability to be identified through itself. In this work, we propose ARTCODE– Adaptive Robust doT matrix barcode, which aims to preserve ART and CODE features in one visual pattern. It works on any surface (paper or electronic displays) and is able to convert any image or any form of human-readable contents (e.g., a picture, a logo, a slogan) into an ARTCODE. It looks like an image which retains human-readable and aesthetically pleasant contents, and in the meanwhile, it acts as a QR code which conveys data bits over the visual channel. The core enablers in ARTCODE are (1) the design of the colored dot matrix for data embedding with little distortion from the original image and (2) a comprehensive error correction scheme which enhances decoding robustness against noises and interferences from the original image in ARTCODE. We implement ARTCODE with the receiver on Android phones and the sender from a PC or a phone (it can be printed in paper). We conduct extensive user survey and experiments for evaluation. It validates the effectiveness and wide applicability of ARTCODE: It works well with all of 197 images randomly downloaded, covering representative categories of the grayscale images, logos, colored ones with low/medium/strong contrasts. The image quality is quite acceptable in a subjective user-perception survey with 50 participants and data communication accuracy achieves as high as 99% in almost all the cases (> 96% raw accuracy in ARTCODE without error detection and other schemes).